(untitled) (Journal of Comparative & International Higher Education, 2022)
The COVID-19 pandemic and the shutdown of schools created disruptions in Vietnamese education, which has not been evaluated to date. This paper provides an analysis of the effect of COVID-19 policies on teaching and learning in higher education in Vietnam. We first contextualize higher education in Vietnam prior to the COVID-19 pandemic. We then present an analysis of the Vietnamese government’s educational policies aimed at controlling virus spread with respect to Vietnam’s inequalities of access to higher education, quality of curriculum and instruction, and institutional autonomy. Our analysis focuses on how government policies can simultaneously respond to the pandemic and moderate prior educational issues. Through this analysis, we contrast the advantages and disadvantages of the policies and highlight the challenges Vietnamese universities face in policy implementation. We conclude this paper by discussing the implications of changes made during the pandemic to comment on higher education in Vietnam post-COVID-19.